Optimasi Penetapan Kadar Akrilamida Yang Ditambahkan Ke Dalam Keripik Kentang Simulasi Secara Kromatografi Cair Kinerja Tinggi - Harahap, Yahdiana; Harmita, Harmita; Simanjuntak, Binsar (Majalah Ilmu Kefarmasian, 2005)
A method by high performance liquid chromatography for the analysis of acrylamide in potato chips, is reported. The retention time for the elution of acrylamide from the C18RP column ranged from 3 to 3,2 minutes, and the eluate was analyzed by UV-VIS detector. A linear response was found for the acrylamide standard tested within the concentration range of 0,8 Â– 10Âµg/ml and the corelation coefficient (r) greater than 0,999, with detection limit 0,06 ppm and quantitative limit 0,19 ppm. Sample preparation was performed by means of solvent extraction using dichlormethane and subsequent re-extraction of the organic solvent with water. This aqueous sample solution was found to be free of any interferences and gave acrylamide and recorveries higher than 90%.